2010
DOI: 10.1007/s11002-010-9122-1
|View full text |Cite
|
Sign up to set email alerts
|

Business strategy, marketing organization culture, and performance

Abstract: Business strategy, Organizational culture, Performance, Configuration theory, Strategy implementation, Miles and snow, Marketing organization,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 34 publications
4
41
0
6
Order By: Relevance
“…Their findings indicated a significant and positive relation between culture and performance. Similarly, Slater, Olson and Finnengan (2011) in their study of business strategy, culture, and performance used a sample of senior marketing managers with five hundred and above employee with the use of the questionnaire as a research instrument. They found that cultural orientation play a role in creating superior performance, evidencing significant and positive relationship between culture and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings indicated a significant and positive relation between culture and performance. Similarly, Slater, Olson and Finnengan (2011) in their study of business strategy, culture, and performance used a sample of senior marketing managers with five hundred and above employee with the use of the questionnaire as a research instrument. They found that cultural orientation play a role in creating superior performance, evidencing significant and positive relationship between culture and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Because the adhocracy culture is characterized by the values of entrepreneurship, innovation, adaptability, propensity for risk, as well as an external orientation, this culture type is the best foundation for a radical product innovation capability (Deshpandé et al., ; Slater, Olson, and Finnegan, ). We next explicate the different components of the adhocracy culture, including customer orientation, competitor orientation, technological orientation, learning orientation, and willingness to cannibalize that are conducive to an effective radical product innovation capability.…”
Section: Components Of a Radical Product Innovation Capabilitymentioning
confidence: 99%
“…Whereas, Berson et al (2005) claimed through their study result that OC is a good mediator. Slater et al (2011) explored that CO had a significant role for generating better performance. Similarly, Mujeeb and Ahmad (2011) empirically assessed the connection between factors of OC and performance management practices, and stated positive significant connection between factors of OC and performance management practices.…”
Section: Organizational Culture (Oc) Sme Performance and The Mediatimentioning
confidence: 99%